INVESTMENT REALIZATION IN INDONESIA ON ECONOMIC GROWTH WITH INTEREST RATE AS MODERATING VARIABLE: Rosdiana - Rosdiana (Samudra Publisher, 2024)
This research aims to explore the relationship between investment and economic growth in Indonesia, considering interest rates as a moderating factor. The research methodology employed includes multiple linear regression and Moderate Regression Analysis (MRA). Through this analysis, the study seeks to provide a deeper understanding of how investment influences economic growth, as well as how interest rates can moderate this relationship. The findings indicate that investment has a significant and positive effect on economic growth in Indonesia. This underscores the importance of investment in driving national economic growth. Furthermore, the study finds that interest rates play a crucial role as a moderating variable. Interest rates can strengthen the relationship between investment and economic growth, indicating that interest rate policies can be effective instruments in optimizing the impact of investment on economic growth. Thus, these findings offer valuable insights for policymakers and business practitioners in designing more effective and sustainable investment strategies. The implications of this research could serve as a foundation for the development of better economic policies in the future, as well as provide guidance for businesses to make more informed decisions in managing their investments. However, the study also acknowledges limitations, such as data constraints and the models used, which could be subjects for further research to enhance understanding of the relationship between investment, interest rates, and economic growth.